PERANCANGAN SISTEM INFORMASI BOOKING BARBER SHOP BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK LARAVEL - Bagaskara, Atanasius Jales Putra; Fauzi, Ahmad (P3M Politeknik Negeri Banjarmasin, 2024)
Currently there are still many barber shops or haircut services that still conventionally serve haircut customers who come to their place without booking a schedule in advance. This can cause a buildup of customers at certain times because there is no booking system that the barber shop applies. So that it makes customers feel bored because they have to wait for service without any certainty of time for them to get a haircut service. Kang Barber is a barber shop schedule booking website that uses the Laravel framework. The design of this information system focuses on making it easy for customers to place orders (booking) barber shop schedules, so that customers can get services directly according to the hours they have ordered without having to wait long or queue. The Kang Barber information system has 3 roles, namely customer, staff and admin. Each has different functions and capabilities in using the website. Customers can order booking schedules after having a registered account, Staff can accept bookings made by customers, and the Admin can fully manage the continuity of the Dashboard such as Create, Read, Update and Delete.